The Tao of travel : enlightenments from lives on the road - Theroux, Paul (Houghton Mifflin Harcourt, 2011)
A collection of writings from Paul Theroux's fifty years of travel. Included are writings from other travelers such as Charles Dickens, Eudora Welty, Anton Chekhov, Ernest Hemingway and many others.